Reservoir Productivity Analysis of Intercalated limestone and Anhydrite Beds in Zagros Folded Belt, Kurdistan Region of Iraq - Rashid, Fraidoon (Kurdistan Journal of Applied Research, 2020)
The Early Jurassic rock of Alan Formation in Barda Rash field has been examined using petrophysical wireline log analysis, drilling stem test, mud logging reports, drilling cutting and core samples for evaluation of reservoir potentiality and fluid production throughout heterogeneous rocks intervals in three exploration and appraisal wells. The Alan Formation consists of intercalation of light, chalky and argillaceous limestone beds with shale layers in the upper part and dominantly anhydrite layers from the middle to the lower parts of the formation. Qualitatively, weak oil shows of light brown to dark brown and blackish heavy oil have been observed while drilling. Furthermore, light brown trace oil has been recorded in the fracture surfaces of the core samples. The wireline log analysis provided an overestimated result for the hydrocarbon bearing interval identification and fluid movability index as the anhydrite layers confused the fluid distribution detection in the drilled interval. However, the combined results achieved from the mud logging reports and drilling stem tests were operated within the drilled intervals shown a limited productivity levels from the limestone beds of the Early Jurassic Alan Formation. The oil production from the studied interval does not exceed 10% and the entire production rates were composed of formation water with a trace amount of gases. As a result, the Early Jurassic Alan Formation can be considered as a tight carbonate reservoir rocks in the Barda Rash field.